Pelatihan Keterampilan Penggunaan Media Mailing List Sebagai Media Belajar Bagi Siswa-Siswa di SMK Sari Buana Makassar - Haeruddin, M. Ikhwan Maulana; Musa, Muh. Ichwan; Musa, Chalid Imran (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2017)
These activities are aiming to provide training on how to utilize email and mailing list as support media systemin learning process to the High School Students on SMK Sari Buana Makassar. Offered methods were participatorylearning method and learning by doing approach. Our activity was highly appreciated and supported by the school?Principal and also the students themselves. It can be seen on their enthusiasms and willingness to attend such trainings. Material and subject utilized are around the basic concept on email and mailing list,  how to start a mailing list forum,how to upload and download files on mailing list, and how to save file on mailing list. The contributive factor on thistraining was the active participation from the students, which could make these activities become easier. However, on theother side, time limit to present and train the student recognized as the problem to this training program